2008
DOI: 10.1111/j.1472-765x.2008.02354.x
|View full text |Cite
|
Sign up to set email alerts
|

Chloraminated drinking water does not generate bacterial resistance to antibiotics in Pseudomonas aeruginosa biofilms

Abstract: Aim:  To determine if exposure of Pseudomonas aeruginosa biofilms to chloraminated drinking water can lead to individual bacteria with resistance to antibiotics. Methods and Results:  Biofilms of P. aeruginosa PA14 were grown in drinking water in a Kadouri drip‐fed reactor; the biofilms were treated with either 0·5 mg l‐1 or 1·0 mg l‐1 of chloramine for 15 or 21 days; control biofilms were grown in water without chloramine. Fewer isolates with antibiotic resistance were obtained from the chloramine‐treated bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
(30 reference statements)
1
5
0
Order By: Relevance
“…Differences in MIC values did not affect classifications of all strains, which were all susceptible to antimicrobial agents according to EUCAST breakpoint guidelines. Similar findings were reported by Jurgens et al [16], Birošová and Mikulášová [2], and Cottell et al [6]. However, our result was not in agreement with those obtained by Karatzas et al [17] or Randall et al [27].…”
Section: Discussionsupporting
confidence: 66%
“…Differences in MIC values did not affect classifications of all strains, which were all susceptible to antimicrobial agents according to EUCAST breakpoint guidelines. Similar findings were reported by Jurgens et al [16], Birošová and Mikulášová [2], and Cottell et al [6]. However, our result was not in agreement with those obtained by Karatzas et al [17] or Randall et al [27].…”
Section: Discussionsupporting
confidence: 66%
“…In a recent study investigating the use of chloraminated drinking water against Ps. aeruginosa biofilm, there was no evidence that the use of chloramine induced an increase in antibiotic resistance (Jurgens et al 2008).…”
Section: Bacterial Biofilms and Resistancementioning
confidence: 97%
“…In one study (Jurgens et al 2008), the aim of which was to determine if exposure of Pseudomonas aeruginosa biofilms to chloraminated drinking water could lead to individual bacteria with resistance to antibiotics, it has been demonstrated that exposure to chloramine does not increase antibiotic resistance in this bacterial species.…”
Section: Biofilmsmentioning
confidence: 99%
“…3E). The major difference from static assays is that the wells are part of a closed system with two outputs, one for the continuous fresh medium supply via an adjusted pump and one for the removal of waste and planktonic cells, while the difference from flow-cell systems lies in the minimal shear forces (93,116).…”
Section: Culturing Biofilms Under Flow Conditionsmentioning
confidence: 99%